A escola como espaço de formação docente : experiências do PNEM no Espírito Santo. - Mariano, Cláudia Simões (2018)
This research aims at the Continuing Education Program of Teachers and Pedagogues of the State of Espírito Santo, a formative action that emerges in the context of the institution of the National Pact for the Strengthening of Secondary Education (Pnem), bringing the principles of the National Curricular Guidelines (Dcnem), 2012, and in the very issues that arise from this stage of basic education, proposing a training that contemplates an integrated approach to the curriculum, distributing the disciplines in areas of knowledge and establishing guidelines, in the expectation of promoting an integral human education for young people in high school. Thus, we seek to contribute to the studies on the continuing education of teachers that, although they are many and common in the Brazilian postgraduate programs, in the state of Espírito Santo, because they are not frequent formations that compile characteristics such as a) the formation in the time of the teaching work, b) the school as a space for continuous training and research, and c) the teacher as a participant subject of his own formation and that of his peers, becomes singular. Our main objective is to verify if and how the teachers and pedagogues of the Pnem Formation, in the day-to-day life of the school, appropriated concepts to (re) invent school daily in the perspective of Certeau, breaking with the accommodation to the that is imposed on them, transforming objects and codes and promoting (re) appropriation of the place of the school by its use, transforming it into a space of formation. In this line, the hypothesis to recover is that the studies of Pnem have transformed a discursive practice into reflexive practice, making possible the materialization in formative practices and contributing, in this way, to the autonomy of the collective of the school. We also had the specific objectives of a) analyzing the uses and appropriations made by teachers about Pnem continuing training in their professionalization, considering the school a space for training; b) to identify how the continued formation of Pnem enabled the teachers to be subjects of their own formation and to contribute to the formation of their peers; c) to record the implications of Pnem in the professionalization of high school teachers in the state public network of Espírito Santo; d) describe the constitution, in the state of Espírito Santo, through public policies, the Continuing Education Program of Teachers and Pedagogues of High School and; e) to map, in the Pnem experience, elements that can contribute to the state policy of teacher training in Espírito Santo. In order to discuss the diversity of contexts in which the formation of Pnem was translated and the complexity of the teachers' "ways of doing" from these contexts and translations, we used an exploratory documentary methodology using as source the database of the SisMédio platform (MEC) ; the monthly reports produced by the regional trainers; the Survey questionnaire, answered by the subjects participating in the training (students, study guides and regional trainers). The results pointed out that Pnem professors and pedagogues took an evolutionary path of epistemological knowledge in the field of basic education curriculum, specifically in the high school stage, to think about the school through the bias of the space of the invention of practices, confirming our initial hypothesis. In addition, among the results of this research, we characterize the formation of the Pnem in Espírito Santo and identify elements that emerge as possibilities of problematizations in the field of the state policy of formation of teachers of the Espírito Santo in the uses and appropriations of the discourses of the reference authors and in the process analysis of the abovementioned documents. This study considers the need to value teacher education, especially through public policies, to promote continuing education for teachers in the space that is their foundation: the school.